THE RELATIONSHIP OF PARENTING PATTERNS WITH THE LEVEL OF LANGUAGE DEVELOPMENT AND SOCIAL DEVELOPMENT OF TODDLERS AT THE SOCIAL DEVELOPMENT OF TODDLERS AT THE TRI WAHYUNI MIDWIFE CLINIC IN SIBOLGA CITY SUB-DISTRICT YEAR 2023 - Sinaga, Ribur; Silaban, Nurmala; Sinuhaji, Lidya Natalia Br; Ridesman; Pasaribu, Riska Susanti (Journal of Public Health Science, 2024)
This study aims to analyze the relationship between parenting styles and the level of language and social development of toddlers at Bidan Tri Wahyuni Clinic, Sibolga Kota District, in 2023. The research method used is an analytical survey with a cross-sectional approach. The study sample consisted of 53 respondents selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using the chi-square test. The results showed a significant relationship between parenting styles and toddler language development (p-value 0.011) as well as social development (p-value 0.021). In conclusion, the parenting styles applied by parents influence toddlers' language and social development. Keywords: Parenting style, Language development, Social development, Toddler